The The Crisis in Red Sea Region: Legal and Socio-Economic Impact on International Commerce - Owoche, Antai Godswill; Aidonojie, Paul Atagamen; Mukhlis , Muhammad Mutawalli; Maskun, Maskun; Tajuddin, Muhammad Saleh; Yeyeng, Andi Tentri (Al-Risalah, 2024)
The continued hijack of shipping vessels on the Red Sea by extremists who claim to have declared war against Israel is one of those blowouts that have been caused by the Israel - Hamas conflict. The journey to unencumbered waters and unfettered shipping access itself has led to several agreements between sovereign states towards the maintenance of seamless high-seas traffic. Unfortunately, non-state actors occasionally come on the scene to wreak havoc and destabilize the fragile peace on international waterways. It is in this regard, that this study tends to examine the Red Sea crisis as it affects global shipping maritime transit and economic growth, especially of African countries vis-a-vis the UN Security Council's role of maintaining world peace and security. The study adopts a doctrinal method of study, the data obtained from primary and secondary sources such as laws and academic literature were analyzed using a descriptive and analytical method. The study therefore found that Rebels are using the pretext of Israel's attacks on Gaza to perpetrate piracy. The Israel - Hamas deadlock has created a deadlocked lose-lose situation for the international community and resulted in new incidents of insecurity within the Red Sea. The study therefore concludes and recommends that the United Nations as the global police especially through the UN Security Council examine all options for securing peace and stability in the Red Sea region as attacks on shipping vessels have global ramifications affecting multiple nationalities and invariably affecting world peace. Keywords: Crisis, Red Sea, Legal, Socio-Economic, International, Commerce.